Virtual Assessment in English Language Teaching during COVID-19 Pandemic: Challenges and Considerations in Bangladesh Perspectives - Md. Nazmul Haque Haque; Md. Mozaffor Hossain (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Background: This study examines the methods of assessing the learners of English Language Teaching (ELT) learners virtually, obstacles both the teachers and students face in virtual assessment, the kind of renovations both teachers and learners have to accommodate for effective virtual assessment, and the imperative suggestions they have in terms of more fruitful and plausible assessment during COVID-19-like pandemics in the context of Bangladesh. Methodology: 10 teachers and 21 students from 5 renowned private universities in Bangladesh participated in the study. And it applied a mixed-method approach consisting of both qualitative and quantitative research methods. Findings: The findings of the study revealed that all the teachers and students go through virtual assessment during the COVID-19 lockdown; the majority of them use Zoom Meeting App and Google Classroom for both summative and formative assessments in the form of mostly virtual viva voce, online assignment, and presentation; virtual assessment is time and money-saving, and has scheduled benefits; its disadvantages include, mainly, unstable internet connection across the country; and most suggest for both teachers’ and students’ training in dealing with technological devices and apps used for virtual assessment. Conclusion: The major results of the research suggest that virtual assessment in ELT in the Bangladeshi context requires substantial technological modifications and renovations. Originality: Since online assessment in ELT, like other academic disciplines, is in function in Bangladesh, better decisions on assessment methodology and, logically, more appropriate assessment policies can be formed. Conforming to this purpose, this research aims to unearth the existing challenges both teachers and learners encounter in virtual assessment and modifications recommended by them.